Bolstering the hegemony of the financial panopticon over emerging markets: A neo-Gramscian reading of the role of ideas, material capabilities and institutions. - Peck, Lawrence W. (University of Ottawa (Canada), 1999)
he impact on the global landscape of the (re-)entry into the international financial system of a large number of middle-income transition and developing countries---the so-called "emerging markets"---has taken many observers by surprise. The Mexican and Asian crises were but two examples of the materialization and worldwide reverberations of inherent contradictions within the emerging market phenomenon; i.e. contradictions between powerful, disembedded and unaccountable financial forces and political forces that are still organized on a territorial basis within relatively weak and vulnerable economics. This thesis deploys a neo-Gramscian constructivist analysis to examine efforts by elements within a nascent transnational historical bloc of financial forces to overcome the risk of a Polanyian double movement to protect emerging market societies. More precisely, as this thesis reveals. there is mounting evidence of an hegemonic project seeking to bolster the emerging synthesis of material capabilities, ideas and institutions appropriate for an eventual hegemonic dominance of financial capital over emerging markets. Eschewing a problem-solving approach to financial matters, this thesis critically examines the roles (i) of material capabilities wielded through collectively allocated financial capital flows, (ii) of the intersubjective meanings given to financial globalization and the subsequent blueprint for commonsensical policymaking, and (iii) of central banks, credit-raters and the IMF in institutionalizing the coercive and consensual power relations at the heart of the emerging hegemonic bloc.
Keywords: Economics, Finance.